A case report of temporomandibular joint tuberculosis in a neonate with eleven years follow-up - Zainab Chaudhary; Prem Kumar Rathod; Abhinav Nehra; Pankaj Sharma (Journal of Oral Biology and Craniofacial Research)
Background: Tuberculosis of the Temporomandibular joint (TMJ) in a neonate is a rare entity. Undiagnosed/mismanaged tuberculosis can disseminate and be life-threatening to the patient. The purpose is to present a case of tubercular osteomyelitis of TMJ in a neonate with eleven years of follow-up. Case presentation: A one-and-a-half-month-old male neonate presented with a firm swelling in front of the left ear for the past 20 days. Ultrasound presented an avascular, hypoechoic lesion of 34*25*25mm. Irregular margins of underlying bone could suggest erosion. Aspiration revealed pus. ZN staining of pus revealed Mycobacterium tuberculosis. After draining the pus, the patient underwent antitubercular therapy. He revisited at ten years of age with a complaint of asymmetry. Although the patient got cured of his tuberculosis, investigations rose to a diagnosis of condylar hypoplasia with ipsilateral coronoid enlargement. A distraction of the mandible improved facial symmetry. Conclusion: Although pus revealed the presence of Acid-fast bacilli, it is not evident until there is a significant bacterial load. Escalation of tests with higher sensitivity is needed to diagnose tubercular osteomyelitis of TMJ. Patients must be made aware of possible sequelae of tubercular osteomyelitis of TMJ and need appropriate management. Oblique osteotomy at the angle and distraction improves both horizontal and vertical components of the mandible and thus improves symmetry. To the best of the author's knowledge, the following is the first case of primary tuberculosis of TMJ in a neonate and with such an extended follow-up.